Implementasi Prinsip 5C Guna Mencegah Resiko Wanprestasi dalam Pemberian Kredit pada Bank Milik Pemerintah Daerah - Dandy Widhianto Putra; Putu Devi Yustisia Utami (Pemuliaan Keadilan, 2024)
This study aims to determine the risks that must be considered by banks before providing credit in order to prevent default and to know the implementation of the 5C principles that are applied when granting credit in PT. BANK BPD BALI Cabang Utama Denpasar, Denpasar. The writing of this research uses the type of empirical research, the location where this research takes place is in PT. BANK BPD BALI Cabang Utama Denpasar, Denpasar. In this research, the law approach and the fact approach are used. The results of the study can be explained that there are two risks that must be considered before giving credit, namely the risk of the bank's reputation and the risk of bank losses, besides that there is also the risk of credit problems. And the implementation used by PT. Bank BPD BALI Cabang Utama Denpasar are interviews and verification as the initial foundation, and the implementation of credit principles using the credit principles of 5C, Character, Capacity, Capital, Collateral and Condition.